Проєктування та розробка інформаційної системи кінотеатру - Ткач, Є. С.; Колесник, О. Б. (ХНУРЕ, 2025)
In today's rapidly developing information technology environment, there are growing requirements for automating business processes in the entertainment sector. Cinemas, as one of the most popular types of entertainment services, strive to provide visІТors with convenient services for choosing movies, buying tickets, and receiving recommendations for new screenings. The implementation of recommendation systems in cinema web applications allows to improve the qualІТy of service by offering viewers personalized offers based on their preferences. The use of modern data analytics technologies allows cinemas to effectively manage their screening program and respond to the needs of visitors.
Keywords: Cinema; кінотеатр